Shared mechanisms across the major psychiatric and neurodegenerative diseases - Thomas S. Wingo; Yue Liu; Ekaterina S. Gerasimov; Selina M. Vattathil; Meghan E. Wynne; Jiaqi Liu; Adriana Lori; Victor Faundez; David A. Bennett; Nicholas T. Seyfried; Allan I. Levey; Aliza P. Wingo (Nature Communications, 2022)
Studying the shared genetic etiology of disease can help improve diagnosis and treatment. Here, the authors find evidence for shared genetic and molecular pathophysiology between several common psychiatric and neurodegenerative diseases using results of 25 GWAS and large-scale human brain transcriptomic and proteomic sequencing.